2003
DOI: 10.1097/00129492-200303000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the Saccular Nerve and of the Vestibular Evoked Myogenic Potential During Vestibular Schwannoma Surgery

Abstract: The combined retrosigmoid and partial labyrinthectomy approach represents an ideal condition to study the influence of the saccular nerve on the origin of the vestibular evoked myogenic potentials. The maintenance of the vestibular evoked myogenic potential responses in our patient supports the concept that the vestibular evoked myogenic potential originates in the saccule and is transmitted in the saccular nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…However, an intact IVN was the prerequsite to elicit any intraoperative muscle response. Our results demonstrate that neither the cochlear nerve nor the SVN contribute to the generation of the VEMPs as suggested earlier (Cazals and Guilhaume, 1985;Magliulo et al, 2003;Patko et al, 2003). Other monitoring methods to map VIIIth nerve subdivisions included the recording of auditory or vestibular brainstem responses upon local electrical stimulation (Miller et al, 1993;Møller, 1995;Shepherd and Javel, 1997;Berryhill and Javel, 2001).…”
Section: Discussionsupporting
confidence: 61%
“…However, an intact IVN was the prerequsite to elicit any intraoperative muscle response. Our results demonstrate that neither the cochlear nerve nor the SVN contribute to the generation of the VEMPs as suggested earlier (Cazals and Guilhaume, 1985;Magliulo et al, 2003;Patko et al, 2003). Other monitoring methods to map VIIIth nerve subdivisions included the recording of auditory or vestibular brainstem responses upon local electrical stimulation (Miller et al, 1993;Møller, 1995;Shepherd and Javel, 1997;Berryhill and Javel, 2001).…”
Section: Discussionsupporting
confidence: 61%
“…Research done in cats 5 suggested this reflex to be of saccular origin, demonstrated by microelectrode testing of the saccular nerve. These findings were supported in humans by the presence of VEMP responses in patients with profound hearing loss (HL), as well as selective ablative cochlear and vestibular lesions 3,4,6 …”
Section: Introductionmentioning
confidence: 89%
“…These findings were supported in humans by the presence of VEMP responses in patients with profound hearing loss (HL), as well as selective ablative cochlear and vestibular lesions. 3,4,6 The VEMP has since been extensively studied in adults, with significant benefit in characterizing superior canal dehiscence syndrome, vestibular neuritis, transtympanic gentamicin labyrinthine ablation, and failed vestibular nerve section. 4,[7][8][9] Some factors are known to effect VEMP testing.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that the p13-n23 waveform component of vestibular evoked myogenic potentials (VEMPs) in humans reflects activation of a vestibulocollic reflex originating in the saccule/inferior vestibular nerve and terminating in the motoneurons of the neck musculature (Colebatch et al, 1994;Halmagyi & Colebatch, 1995;Murofushi et al, 1996Murofushi et al, , 1998Todd et al, 2000;Ochi & Ohashi, 2001;Al-Sebeih & Zeitouni, 2002;Sheykholeslami & Kaga, 2002;Magliulo et al, 2003). As a clinical procedure, VEMP testing has provided information regarding otolith and inferior vestibular nerve function in healthy individuals as well as patients with Ménière's disease (Robertson & Ireland, 1995;deWaele et al, 1999;Shojaku et al, 2001;Young et al, 2003), vestibular neuritis (Ochi et al, 2003;Brantberg et al, 2003;Monobe & Murofushi, 2004), vestibular schwannoma (Murofushi et al, 1998;Matsuzaki et al, 1999;Tsutsumi et al, 2001), and superior semicircular canal dehiscence (Brantberg et al, 1999;Brantberg et al, 2004).…”
Section: Sumariomentioning
confidence: 99%